Discontinuation of Hemodialysis in a Patient with Anti-GBM Disease by the Treatment with Corticosteroids and Plasmapheresis despite Several Predictors for Dialysis-Dependence. (11th October 2017) - Fujigaki, Yoshihide; Morimoto, Chikayuki; Iino, Risa; Taniguchi, Kei; Kawamorita, Yosuke; Asakawa, Shinichiro; Toyoki, Daigo; Miyano, Shinako; Fujii, Wataru; Ota, Tatsuru; Shibata, Shigeru; Uchida, Shunya
Abstract : A 26-year-old man highly suspected of having antiglomerular basement membrane (GBM) disease was treated with corticosteroid pulse therapy 9 days after initial infection-like symptoms with high procalcitonin value. The patient required hemodialysis the next day of the treatment due to oliguria. In addition to corticosteroid therapy, plasmapheresis was introduced and the patient could discontinue hemodialysis 43 days after the treatment. Kidney biopsy after initiation of hemodialysis confirmed anti-GBM disease with 86.3% crescent formation. Physician should keep in mind that active anti-GBM disease shows even high procalcitonin value in the absence of infection. To pursue recovery of renal function, the challenge of the immediate and persistent treatment with high-dose corticosteroids plus plasmapheresis for highly suspected anti-GBM disease is vitally important despite the presence of reported predictors for dialysis-dependence including oliguria and requiring hemodialysis at presentation.